G606(P) Clinical impact of rapid identification of pathogens in csf of general paediatric patients. (25th October 2020) - Riordan, A; Wade, L; Waugh, L; Shaw, F
Abstract : Rapid diagnosis and treatment of meningitis and encephalitis are advised to help reduce morbidity and mortality. However, few children treated for suspected central nervous system (CNS) infection have confirmed infection. FilmArray® Meningitis/Encephalitis (FA- M/EP) Panel is a multiplex PCR system that can rapidly test for common CNS pathogens. We aimed to assess the clinical impact of FA-M/EP in general paediatric patients. From 6th June 2016 FA-M/EP was performed on cerebrospinal fluid (CSF) when requested by the general paediatric consultant. Following an interim review the following changes were made: FA–M/EP was not performed on CSF that was visibly blood stained FA–M/EP was only performed if enough sample was available to send for confirmatory vial PCR. FA–M/EP was performed in in a separate room in the laboratory. Data was collected for a further 12 months following these changes (October 2016 – October 2017). Results: FA-M/EP was performed on 43 children during June-Oct 2016. Results of FA-M/EP were helpful in managing 16 (37%) children – see table 1 . In four children results (9%) FA-M/EP led to prolonging of hospital admission (HSV, pneumococcus, Haemophilus), increasing the length of stay by 17 days. No bed days were saved overall in this period. FA-M/EP was performed on 63 samples from 59 children during the next 12 months (Oct 2016 – Oct 2017). Results of FA-M/EP were helpful in managing 30 (48%) episodes; saving 25 Bed days for 13 episodes. In one child results from FA-M/EP led to prolonging hospital admission by 2 days (Varicella). All positive results by FA-M/EP for HSV1 HSV2, Varicella zoster virus, Haemophilus and pneumococcus did not correlate with the clinical features and were likely false positives. Conclusions: FA-M/EP was useful in rapid detection of enteroviral meningitis and ruling out HSV encephalitis. However false positive results for HSV, VZV, Haemophilus and pneumococcus led to prolonged admissions. In general paediatric patients with a low risk of meningitis/encephalitis rapid tests which give false positive results may lead to unnecessary treatment and prolonged admissions. These tests should be used with caution in this population.